2022
DOI: 10.3389/fmed.2022.831541
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril-Valsartan Increases Ultrafiltration in Patients Undergoing Peritoneal Dialysis: A Short-Term Retrospective Self-Controlled Study

Abstract: AimThere are few data about the effectiveness and safety of angiotensin receptor-neprilysin inhibitor (ARNI) sacubitril-valsartan in end-stage renal disease (ESRD) patients undergoing peritoneal dialysis (PD). The present study was conducted to evaluate the association between sacubitril-valsartan treatment and peritoneal ultrafiltration (PUF) in PD patients.Methods and ResultsForty-seven ESRD patients undergoing PD for at least 3 months without severe congestive heart failure (CHF) were included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…, 34 2022 China 2020–2021 Retrospective, observational self-controlled study 50–200 mg/day 6 mo 54 Mean 50.9 (SD 14.6) 29 (53%) HD HFrEF, LVEF <40% B-blocker: n = 51 Zhang et al. , 35 2022 China 2020–2021 Retrospective, observational self-controlled study 100 mg twice a day 7 d 47 Mean 45.9 (SD 12.4) 28 (60%) PD Nonspecified Hypertension: n = 42, Diabetes, n = 10 ACEI/ARB: n = 27, Diuretic: n = 12 Zhao et al. , 36 2022 China 2019–2021 Retrospective, observational cohort study 100 mg twice a day 3 mo 122 Mean 49.13 (SD 15.4) 75 (75%) HD Nonspecified Hypertension: n = 69, Diabetes: n = 17, CAD: n = 13 ACEI, angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; CAD, coronary artery disease; d, day; HD, hemodialysis; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection; IQR, interquartile range; LVEF, left ventricular ejection fraction; MCA, mineralocorticoid antagonist; mo, month; PD, peritoneal dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 34 2022 China 2020–2021 Retrospective, observational self-controlled study 50–200 mg/day 6 mo 54 Mean 50.9 (SD 14.6) 29 (53%) HD HFrEF, LVEF <40% B-blocker: n = 51 Zhang et al. , 35 2022 China 2020–2021 Retrospective, observational self-controlled study 100 mg twice a day 7 d 47 Mean 45.9 (SD 12.4) 28 (60%) PD Nonspecified Hypertension: n = 42, Diabetes, n = 10 ACEI/ARB: n = 27, Diuretic: n = 12 Zhao et al. , 36 2022 China 2019–2021 Retrospective, observational cohort study 100 mg twice a day 3 mo 122 Mean 49.13 (SD 15.4) 75 (75%) HD Nonspecified Hypertension: n = 69, Diabetes: n = 17, CAD: n = 13 ACEI, angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; CAD, coronary artery disease; d, day; HD, hemodialysis; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection; IQR, interquartile range; LVEF, left ventricular ejection fraction; MCA, mineralocorticoid antagonist; mo, month; PD, peritoneal dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, data from Zhang et al. 35 was not sufficient for the analysis of LVEF changes. As depicted in Supplementary Figure S1 , our analysis revealed no significant difference between the HD and PD groups ( P = 0.76).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increasing attention has been paid to the role of ARNI in HF patients complicated with CKD. For ESRD in dialysis patients, a study had shown that LCZ696 treatment can increase short‐term peritoneal ultrafiltration in PD patients, but did not increase 24 h urine volume, which demonstrated the role of LCZ696 in water removal and BP control in PD patients 17 . Therefore, it is possible for LCZ696 to play a beneficial role in CHF patients with ESRD on dialysis in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang F et al. conducted a short-term observation of the effect of SV on peritoneal ultrafiltration and found that SV increased ultrafiltration by 66.4 mL/24h in PD patients within 7 days after its use [ 26 ]. Our study had similar results, and moreover, we had a much longer follow-up time which proved that the effect of SV on increasing peritoneal ultrafiltration was sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…It is distributed ubiquitously in the tissue including epithelia, fibroblasts, and kidney and it could also be in the soluble form in the plasma [ 27 , 28 ]. Since the peritoneum is covered by epithelium and rich in the vasculature, the inhibition of neprilysin in PD patients might result in the dilation of blood vessels, which might help increase the peritoneal ultrafiltration [ 26 ]. But the exact mechanism involved requires further exploration.…”
Section: Discussionmentioning
confidence: 99%